Edukasi Pemanfaatan Bahan Alam Menjadi Sediaan Farmasi pada Masyarakat Desa Sukaraja Kecamatan Sepaku Kab. Penajam Paser Utara - Islamudin Ahmad; M. Arifuddin; Nurul Muhlisa Mus; Faizatun Maulidha; Karisman Karisman; Michael Rendy Yakubus; Aji Ayatullah; Dandy Zwageri; Erwin Samsul (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
Traditional medicine has the opportunity to be used in preventive promotive efforts, especially to maintain immunity as one of the cultural traditions of the community that has been passed down from generation to generation by utilizing local wisdom. The diversity of medicinal plants that exist in East Kalimantan encourages the community to play an active role in processing and developing these plants into products that can help maintain health. One village that has a vision and mission to improve the quality of agricultural, animal husbandry, plantation and fisheries as well as developing human resources in the village is Sukaraja Village. Education on the utilization of natural medicinal substances into pharmaceutical preparations is carried out using power point media using the lecture method. This activity ran smoothly which was shown by the enthusiasm of the people of Sukaraja Village in listening to explanations and actively asking the speakers, especially regarding various kinds of medicinal plants that have the potential to be made into pharmaceutical preparations so that they are able to develop products based on natural ingredients in a variety of ways and can become a mainstay commodity by utilizing plants originating from natural materials around Sukaraja Village.